13 Molecular and Clinical Characterization of Early-Onset Renal Cell Carcinoma (eoRCC): A Real-World Multi-Omics Analysis - Hedyeh Ebrahimi; Scott Haake; Michelle Weitz; Adam J Dugan; Unnati Jariwala; Jacob Mercer; Alan Tan; Sumanta Pal; Brian Rini; Alexander Chehrazi-Raffle (The Oncologist, 2026)
Abstract Background The rising incidence of young-onset cancers is a global public health concern. From 2010-2019, eoRCC had the third largest increase after breast and colorectal cancers. However, molecular drivers and survival implications for eoRCC remain unclear. This analysis compares somatic, germline, immune, transcriptomic, and clinical features of eoRCC vs. typical-onset RCC (toRCC) using a multi-omic real-world dataset. Methods The Tempus Lens Platform (Tempus AI, Inc., Chicago, IL) was used to query the multimodal de-identified database to identify RCC patients (pts) with xT (DNA) and xR (RNA) sequencing with tumor purity ≥30%. Pts with clear cell RCC (ccRCC; n = 1,842), papillary RCC (pRCC; n = 242), and chromophobe RCC (chRCC; n = 117) were stratified by age at diagnosis as eoRCC (18 to ≤ 46 years) and toRCC (>46 years). Demographic, clinical, somatic, germline genomic features, and transcriptomic profiles were compared. Tumor immune infiltration was inferred from the transcriptomic RNAseq data (quanTIseq). Differential gene expression and pathway enrichment used log2 (TPM+1) normalized RNA-seq data against Hallmark and GOBP gene sets. Results Among pts with ccRCC (eoRCC: n = 211, 11.5%; toRCC: n = 1,631, 88.5%), pts with eoRCC were more often Black/African American (8.7% vs. 3.8%, p = 0.029) and Hispanic/Latino (32% vs. 17%, p < 0.001) compared to pts with toRCC. Germline alterations occurred in 11.3% eoRCC pts and 7.3% in toRCC (q = 0.5), with no age-enriched variants. Early-onset ccRCC had lower somatic alteration rates in PBRM1 (21% vs. 43%, q < 0.001), SETD2 (13% vs. 25%, q < 0.001), and KDM5C (6% vs. 12%, q = 0.025), while VHL alteration rates were identical (76%). Transcriptomic profiling revealed upregulation of hypoxia- and VEGFR-signaling pathways in early-onset ccRCC (q < 0.05). In contrast, immune-related pathways (IFNgamma/IFNalpha, IL6/JAK/STAT) and cell cycle regulators (E2F, mTOR) were downregulated (q < 0.05). Immune cell composition analysis indicated reduced infiltration of M1 macrophages in eoRCC vs. toRCC (p = 0.003). Among pts with pRCC (eoRCC: n = 35, 14.5%; toRCC: n = 207, 85.5%) and chRCC (eoRCC: n = 28, 23.9%; toRCC: n = 89, 76.1%), baseline characteristics were similar, and no significant differences in somatic or germline alterations or immune cell infiltration were observed. However, in the chRCC cohort, the oxidative phosphorylation pathway was upregulated in eoRCC, with concomitant downregulation of the epithelial-mesenchymal transition pathway (q < 0.05). In the pRCC cohort, oxidative phosphorylation was downregulated in eoRCC (q < 0.05). Conclusions Age-stratified analysis showed that among patients with ccRCC, eoRCC has distinct features with more non-white racial/ethnic groups. Early-onset ccRCC is associated with distinct biological phenotypes, exemplified by upregulation of the hypoxia/VEGF pathway and downregulation of immune, inflammatory, and cell cycle pathways. These hypothesis-generating findings highlight potential age- and histology-specific therapeutic targets and the need to explore age-adapted treatment strategies for this unique and growing population.